EL PAPEL DE LA NORMA EN LA COLABORACIÓN INTERTERRITORIAL: PROPUESTAS DE REFORMA - Ignacio González García (Revista d'Estudis Autonòmics i Federals, 2016)
Fluent and proper relations of intergovernmental cooperation between the different subjects that compound a complex state is an essential part for their successful articulation. The norm is the backbone of these relationships, but the political will of the parties is the determining factor in their success. This does not mean, however, that the various territorial authorities can escape from the requirements deriving from the constitutional principles. Thus, the role of doctrine should be limited to ensure the technical improvement of those specific collaboration tools they need so as to be truly effective, while complying at the same time with such constitutional requirements. In this paper I present different reform proposals for the Presidents' Conference, the involvement of regional parliaments in holding inter-territorial agreements and the conflict concerning the involvement of vertical agreements. Keywords: collaboration; cooperation; autonomous regions; relationships; agreements; Presidents Conference; reforms.